Aliran-Aliran Filsafat Barat Kontemporer (Postmodernisme) - Lailatul Maskhuroh (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2021)
Philosophy in the contemporary era has different characteristics from the previous era. Some of its characteristics, namely departing from humans who live in this age are very careful in following scientific development methods as well as examining language, meaning, symbols and emotions, human life attitudes. Technology dominates in this era so that many philosophers who are realists and the human soul experience emptiness. It can be said that the distinctive feature of this contemporary philosophy is that it does not have a flow form but continues to conduct studies and propose solutions that are continuously updated, a school of philosophy emerged in the postmodernism era, namely phenomenology and existentialism, analytical philosophy and philosophy of language, critical philosophy, postmodernism, while those which are used as a discussion in the era of Western contemporary philosophy and its surroundings, namely logical positivism, neomarxism, pragmatism, Neo-kantianism, phenomenology and existentialism, philosophy of life, postmodernism, contemporary atheism, hermeneutics.